Polymorphisms in Plasmodium falciparum chloroquine resistance transporter (Pfcrt) and multidrug-resistant gene 1 (Pfmdr-1) in Nigerian children 10 years post-adoption of artemisinin-based combination treatments. Issue 4 (March 2021) - Kayode, Adeyemi T.; Akano, Kazeem; Ajogbasile, Fehintola V.; Uwanibe, Jessica N.; Oluniyi, Paul E.; Bankole, Bolajoko E.; Eromon, Philomena J.; Sowunmi, Akintunde; Folarin, Onikepe A.; Volkman, Sarah K.; McInnis, Bronwyn; Sabeti, Pardis; et al.
Graphical abstract: Highlights: Over 50% of parasites considered in this study harboured the mutant C72 I74 E75 T76 haplotype of the Pfcrt gene. As it stands, CQ cannot be re-introduced as treatment for malaria in Nigeria if ACT resistance were to emerge. 21.1% of parasites had the Pfmdr- 1 mutant N86 F184 haplotype in Nigeria which suggests an increase in prevalence. The three ACTs considered in this study, i.e. AA, AL and DHP, are still effective antimalarials with DHP slightly superior. Abstract: The emergence and spread of Plasmodium falciparum parasites resistant to artemisinin derivatives and their partners in southeastern Asia threatens malaria control and elimination efforts, and heightens the need for an alternative therapy. We have explored the distribution of P. falciparum chloroquine resistance transporter ( Pfcrt ) and multidrug-resistant gene 1 ( Pfmdr- 1) haplotypes 10 years following adoption of artemisinin-based combination therapies in a bid to investigate the possible re-emergence of Chloroquine-sensitive parasites in Nigeria, and investigated the effect of these P. falciparum haplotypes on treatment outcomes of patients treated with artemisinin-based combination therapies. A total of 271 children aged <5 years with uncomplicated falciparum malaria were included in this study. Polymorphisms on codons 72–76 of the Pfcrt gene and codon 86 and 184 of Pfmdr -1 were determined using the high resolution melting assay. Of 240 (88.6%) samples successfully genotyped with HRM for Pfcrt, wildtype C72 M74 N75 K76 (42.9%) and mutant C72 I74 E75 T76 (53.8%) were observed. Also, wildtype N86 Y184 (62.9%) and mutant N86 F184 (21.1%), Y86 Y184 (6.4%), and Y86 F184 (0.4%) haplotypes of Pfmdr -1 were observed. Measures of responsiveness to ACTs were similar in children infected with P. falciparum crt haplotypes (C72 I74 E75 T76 and C72 M74 N75 K76 ) and major mdr -1 haplotypes (N86 Y184, N86 F184 and Y86 Y184 ). Despite a 10 year gap since the malaria treatment policy changed to ACTs, over 50% of the P. falciparum parasites investigated in this study harboured the Chloroquine-resistant C72 I74 E75 T76 haplotype, however this did not compromise the efficacy of artemisinin-based combination therapies. Should complete artemisinin resistance emerge from or spread to Nigeria, chloroquine might not be a good alternative therapy.